Knowledge of, Perception of, and Attitude towards Uterine Fibroids among Women with Fibroids in Lagos, Nigeria - M. A. Adegbesan-Omilabu; K. S. Okunade; A. Gbadegesin (Scientifica)
Objectives. The study was to assess the level of knowledge of, perception of, and attitude towards uterine fibroids among women diagnosed with the condition. Methods. It is a cross-sectional descriptive study carried out among women diagnosed as having uterine fibroids in two gynaecological clinics in Lagos, Nigeria. Eligible women were recruited and a structured interviewer-administered questionnaire was used to collect the required information. Statistical analysis of data was done using EPI Info 2008. Results. Knowledge of fibroids was reported in 98.6% of the respondents and the information on uterine fibroids was obtained from radio, parents/relatives, health workers, and television in 29%, 27.3%, 18.7%, and 18.3%, respectively, by the respondents. Most of the women believed that being black, being nulliparous, or having positive family history predisposes women to having uterine fibroids. Up to 69.0% of the respondents believed that fibroid is a spiritual problem and many thought it requires spiritual healing. Fear of complications of surgery keeps most sufferers away from the hospital until fibroids become advanced or associated with complications. Conclusion. Awareness of uterine fibroids is high, but correct knowledge on aetiology and proper treatment is low. Intensive enlightenment of the populace using the mass media by trained personnel is recommended.